2004
DOI: 10.1063/1.1762704
|View full text |Cite
|
Sign up to set email alerts
|

Microscale polymeric helical structures produced by electrospinning

Abstract: Microscale helical coils consisting of a composite of one conducting and one nonconducting polymer were produced using electrospinning. The nonconducting polymer was poly(ethylene oxide) and the conducting polymer was poly(aniline sulfonic acid). The coil structures were studied over a range of processing conditions and fiber composition. The data suggest that the helical structures are formed due to viscoelastic contraction upon partial neutralization of the charged fibers. Polymeric microcoils may find appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(61 citation statements)
references
References 8 publications
0
61
0
Order By: Relevance
“…Helical or curled fibers have also been observed on special collectors such as a nail tip, which concentrates the electric field [145]. The mechanism for the observed fiber morphology has been proposed to be contraction or uniform mechanical buckling of the fiber jet upon contact with the collector [133,134,136,138,146,147]. The converging electrical field drags the front part of the electrospinning jet toward the collector tip by increasing the bending instabilities of the charged jet.…”
Section: Helicalmentioning
confidence: 99%
See 1 more Smart Citation
“…Helical or curled fibers have also been observed on special collectors such as a nail tip, which concentrates the electric field [145]. The mechanism for the observed fiber morphology has been proposed to be contraction or uniform mechanical buckling of the fiber jet upon contact with the collector [133,134,136,138,146,147]. The converging electrical field drags the front part of the electrospinning jet toward the collector tip by increasing the bending instabilities of the charged jet.…”
Section: Helicalmentioning
confidence: 99%
“…Some examples of these type of bicomponent fibers are poly(p-phenylene vinylene) (PPV)/PVP fibers or PEO and the conductive polymer poly(aniline sulfonic acid). The authors suggest that the helical micro-coils observed were formed spontaneously upon contact with a conducting substrate due to the viscoelastic contraction of the fiber upon partial charge neutralization [132,133]. Lin et al developed a microfluidic electrospinning nozzle for the side-by-side deposition of two polymers to make a bi-component fiber [134].…”
Section: Helicalmentioning
confidence: 99%
“…The helical structures were formed as a result of viscoelastic contraction upon partial neutralization of the charged fibers. Such polymeric microcoils may find application sin microelectromechanical systems, advanced optical components, and drug delivery systems [36].…”
Section: Coaxial Nanofibers and Nanotubes Of Panimentioning
confidence: 99%
“…Kessick et al 113 Prepared helical coils composed of a polyaniline and PS by electro spinning. Electronic polymers have been electrospun in order to develop nano scale electronic machines.…”
Section: Electronic Applicationsmentioning
confidence: 99%